The Local Aerosol Emission Effect on Surface Shortwave Radiation and Temperatures. (23rd March 2019) - Freychet, N.; Tett, S. F. B.; Bollasina, M.; Wang, K. C.; Hegerl, G. C.
Abstract: The local aerosol emission effect is investigated by comparing two numerical simulations (1982–2016) with the U.K. HadGEM3‐GA6 model nudged to the same ERA‐Interim circulation. One includes full historical Coupled Model Intercomparison Project Phase 5 RCP4.5 aerosol emission changes while the second uses a monthly aerosol climatology from 1982. At global scale, the emission scenario does not change the mean surface energy balance, but it shows strong regional contrasts. Thus, we focus on regions where the change in emission has been the largest: North America, Europe, India, and China. No clear impact on temperature trends is found over China although aerosol emissions have increased in recent decades. This could be explained by a stronger role of meteorology in this region rather than direct surface heating, and also by a more limited change in aerosol optical depth compared to regions such as Europe. Other regions show clearer responses to aerosol effect, consistent with previous studies: cooler maximum temperatures (with historical emission compared to fixed emissions) where emissions have increased (North‐East of India) and warmer maximum temperatures where emissions have decreased (Europe). However, in each region, the interannual variability in temperatures is strongly controlled by the circulation. Precipitation is also locally decreased (0.5 mm/day) over North India during summer due to a reduction of moisture convergence in the boundary layer (where no nudging is applied). Based on these simulations, we suggest that radiation‐driven aerosol emission impacts on local surface temperature and precipitation are not linear and can be mitigated or cancelled by the local dynamics. Key Points: Nudged simulation (1982–2016) is used to force the model dynamics and isolate the effect of aerosol emissions from the circulation feedback The effect of aerosol emissions on temperatures over China is weak, possibly due to lower AOD changes and overshadowed by meteorology Other regions have more consistent response between radiation and temperatures; the effect on precipitation is however very limited